Pemanfaatan Limbah Tepung Sagu (Onggok) Menjadi Pakan Ternak di Desa Ngemplak Kidul Kabupaten Pati - M. Syaipul Hayat; Ummi Kaltsum (Perkumpulan Kualitama Edukatika Indonesia, 2021)
The aim of IbM of tapioca waste processing to be livestock feed is to provide skills producing fodder to partners. Partners of this IbM are the housewifes of RT 1 RW 1 and RT 3 RW 1 in Ngemplak Kidul Pati. The majority of local residents depends life as a laborer pelvis cassava seasonally. In fact, in this area there are several producer of corn starch that produced sago waste. About 10.5 tons of sago waste is produced by two producers every day. The solution of the problems is the utilization of sago waste into useful thing and economic valued, so that it can be an alternative incoming source for residents. Service activities included coordination with the RT, socialization program to partners, training of feed manufacture, business management training, and the production of livestock feed. Livestock feed was made by mixing tapioca waste, salt, molasses, water, urea, ammonium sulfate, and fish extracts. The next process was fermentation for 6 days and drying. The results of this IbM program is livestock feed ready to be marketed.